Strategi Konvergensi TV ONE Menghadapi Era New Media - Taufan Hariyadi (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Abstract : Conventional news television media is increasingly facing a hard challenges. The use of new media such as YouTube, Facebook, Instagram are increasingly popular in the society. A number of studies in the world have shown that the use of new media continues to take on the role and function of conventional media. People are encouraged to make their own news and then broadcast it on their social media accounts. This condition makes news no longer monopolized by news television. Facing this condition, news television must improve and adapt to convergence. This study aims to find out how tvOne as one of the conventional news television faces new digital media attacks. What are the steps that tvOne has done in adapting and converging? Based on qualitative research through observation on tvOne for 5 months, supported by indepth interviews with several key informants from supervisor level to editor in chief, the results descriptively showed that tvOne as the news television has been converging since 2011. Convergence occurs in two stages, that was convergence through hardware communication technology and convergence through new media. New media convergence drives tvOne to create new content specifically for new media platforms with a new target audience that is not a terrestrial audience. The results of this study portrays that tvOne terrestrial content can be distributed into a new media platforms, but not on contrary.